APPLICATION OF IMPRECISE MODELS IN ANALYSIS OF RISK MANAGEMENT OF SOFTWARE SYSTEMS - Kharchenko, Volodymyr; Alexeiev, Oleg; Rudas, Sergiy; Kozhokhina, Olena (Proceedings of National Aviation University (archive), 2017)
The analysis of functional completeness for existing detection systems was conducted. It made it possible to define information systems with a similar feature set, to assess the degree of similarity and the matching degree of the means from the "standard" model of risk management system, that considers the recommended ICAO practices and standards on aviation safety, to justify the advisability of decision-making support system creation, using imprecise model and imprecise logic for risk analysis at aviation activities. Imprecise models have a number of features regarding the possibility of taking into account the experts’ intuition and experience, the possibility of more adequate flight safety management processes modelling and obtaining the accurate decisions that correlate with the initial data; support for the rapid development of a safety management system with its further functionality complexity increase; their hardware and software implementation in control systems and decision making is less sophisticated in comparison with classical algorithms.